Pengaruh Shift Work, Burnout dan Distress Terhadap Produktivitas Kerja Karyawan Bagian Produksi pada PT. Delta Dunia Textil1 Karanganyar - Septiana Luthfi Muthohar; Putri Oktovita Sari (PENG: Jurnal Ekonomi dan Manajemen, 2026)
This study is a survey research conducted on employees of PT. Delta Dunia Textil 1 Karanganyar. The purpose of this study is to examine the effect of shift work, burnout, and distress on the work productivity of production employees. The type of data used is quantitative data with primary data sources. Data were collected through questionnaires distributed to respondents who met the research criteria. The population in this study consisted of 1,100 employees, with a sample of 100 respondents determined using purposive sampling. The research instrument was tested for validity and reliability. Data analysis techniques included descriptive analysis, multiple linear regression, t-test, F-test, and coefficient of determination (R²).The results of the study show that partially: (1) shift  work has a positive but insignificant effect on work productivity with a p-value = 0.648 > 0.05; (2) burnout has a positive and significant effect on work productivity with a p-value = 0.000 < 0.05; and (3) distress has a positive but insignificant effect on work productivity with a p-value = 0.495 > 0.05. Simultaneously, shift work, burnout, and distress have a positive and significant effect on employee productivity. The coefficient of determination (R²) test results indicate that the independent variables explain 51.8% of the variation in work productivity, while the remaining 48.2% is influenced by other factors outside this study.